AIRFIELD RUNWAY LIGHTING EFFICIENCY ESTIMATING BASED ON SIMULATING LANDING PROCESS IN LOW VISIBILITY - Yu. T. Zyryanov; V. M. Dmitriev (Научный вестник МГТУ ГА, 2016)
The paper presents an approach to solving important scientific application at the evaluation of the effectiveness of airfields runway lighting in low visibility conditions using the integral index-based fashion.